Qualidade tecnológica da cana-de-açúcar sob adubação com torta de filtro enriquecida com fosfato solúvel - Santos, Diego H. [UNESP]; Silva, Marcelo de A.; Tiritan, Carlos S.; Foloni, Jose S. S.; Echer, Fábio Rafael [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2011)
The study had the objective to evaluate the effect of the fertilization with filter cake enriched with soluble phosphate on the sugar yield. The experiment carried at Presidente Prudente-SP, used a randomized complete block design, in the factorial scheme 5 x 4, where the first factor consisted of doses of filter cake (0; 0.5; 1.0; 2.0 and 4.0 t ha(-1)) and the second, doses of phosphorus fertilizer (0, 50, 100, 200 kg ha(-1) of P2O5), with 4 replicates, totaling 80 plots. The results indicated that phosphorus applied in planting furrows improves the quality of sugarcane raw matter by increasing the levels of soluble solids, total reducing sugars and sucrose in the stalks. The phosphorus also increases the productivity of sugar. The filter cake applied in planting furrow has the potential to partially replace the chemical fertilization with phosphate aiming to improve the quality and the productivity of sugar. The best combination was filter cake at dose between 2.6 and 2.7 t ha(-1) combined with dose between 160 and 190 kg P2O5 ha(-1) for obtaining best response of soluble solids and productivity of sugar.
Technological quality of sugarcane under fertilization with filter cake enriched with soluble phosphate
Keywords: Saccharum spp.; organic-mineral fertilizers; triple superphosphate; productivity of sugar